Активність полідисперсних мінеральних компонентів та їх роль у формуванні структури та міцності цементів - Соболь, Х. С.; Марків, Т. Є.; Петровська, Н. І.; Гуняк, О. М.; Sobol, Kh. S.; Markiv, T. Ye.; Petrovska, N. I.; Hunyak, O. M. (Видавництво Львівської політехніки, 2019)
Встановлено, що цеолітовий мінеральний компонент порівняно з перлітовим компонентом характеризується вищою пуцоланічною активністю. Показано, що за коефіцієнтом пуцоланічної активності полідисперсний цеолітовий компонент перевершує тонкодисперсний. Доведено, що висока міцність цементу із полідисперсним цеолітовим компонентом пов’язана з його активною роллю у формуванні мікро- та мезоструктури тверднучої системи. Підтверджено формування щільної, дрібнопористої та дрібнокристалічної структури цементного каменю зі вмістом полідисперсного цеоліту, з утворенням голчасто-волокнистих гідросилікатів CSH(I), які кольматують пори і армують контактні зони. Обґрунтовано функцію полідисперсного цеолітового компонента у створенні гідратаційного резерву води. Підтверджено роль полідисперсності складу цеоліту при реалізації його властивостей як активної мінеральної добавки та оптимізації гранулометричного складу на рівні мезоструктури.

Among the large number of well-known and widely used active mineral additives of natural and artificial origin, zeolitic tuffs, an aluminosilicate with microporous framework structure, are of a great interest. Porous active mineral additives also include expanded perlite, which is obtained by thermal treatment of natural perlite – alkaline aluminum silicate glass. The activity of zeolite and perlite is connected to their ability to react with Са(ОН)2 and SO42-. In addition to the composition, their dispersion also has a significant impact on the activity level of mineral additives. Therefore, the main goal of this work is to study of the peculiarities of hydration processes and structure formation of Portland cement with porous active mineral additions of different particle size composition. It has been established that the polydisperse zeolite component is characterized by higher activity in comparison with the polydisperse perlite component. It is shown that the coefficient of pozzolanic activity of polydisperse mineral components exceeds fine dispersed ones. There is no correlation between the level of activity by absorption of CaO of porous mineral additives of different dispersion and strength of Portland cement. It is proved that high strength of cement with a polydisperse zeolitic component is related to its active role in the formation of the microstructure and mesostructure of the hardening system. The formation of a dense, fine-porous and fine-crystalline structure of cement stone has been confirmed, with formation of fibrous needle-like hydrosilicates CSH (I), which lead to colmatation of pores and reinforcement of contact zones. The function of a polydisperse zeolitic component in the creation of water reserve for hydration is substantiated. The role of polydispersity of the composition of zeolite in the realization of its properties as an active mineral additive and optimization of granulometric composition at the level of the mesostructure has been confirmed. Therefore, the application of fine and superfine grinding for zeolite as an active mineral additive in the production of Portland cement needs to be re-evaluated.
Activity of polydisperse mineral components and their role in formation of structure and strength of portland cements
Keywords: пуцоланічна активність; цеоліт; перліт; полідисперсні компоненти; мезоструктура; pozzolanic activity; zeolite; perlite; polydisperse components; mesostructure; 666.943